Atomic Layer Deposition of Pt Nanoelectrode Array for Polymer Electrolyte Fuel Cells. Issue 7 (15th March 2019) - Sabarirajan, Dinesh C.; George, Thomas Y.; Vlahakis, James; White, Robert D.; Zenyuk, Iryna V.
Abstract : This study presents thin-film electrode design for polymer electrolyte fuel cells (PEFCs) prepared by atomic layer deposition (ALD). Due to structural alignment and controlled pore sizes, this Pt ALD nanoelectrode array is a promising model ionomer-free electrode for transport and reaction kinetics studies. The ALD fabrication process is used to deposit monolayers of Pt onto a sacrificial substrate by dissociative chemisorption in a self-assembling reaction. A novel thermal exposure mode is used to deposit Pt nanostructures onto anodized aluminum oxide (AAO) discs using trimethylcyclopentadienylmethylplatinum (IV) and oxygen gas as precursors. This technique provides additional time for surface reactions and allows higher penetration of the precursor into the AAO disc. By varying exposure time the electrode thickness is varied. The model electrode is used with metallic gold interlayer and varied relative humidity to delineate ion transport mechanisms during detection of electrochemical surface area with cyclic voltammetry (CV) and CO-stripping. This study shows that adsorbed hydrogen surface diffusion is an unlikely transport mechanism during CV and that proton surface migration is a more feasible mechanism.